Highly tough, degradable, and water-resistant bio-based supramolecular plastics comprised of cellulose and tannic acid. Issue 13 (15th March 2023) - Sun, Haoxiang; Fang, Xu; Zhu, Youliang; Yu, Zhuochen; Lu, Xingyuan; Sun, Junqi
Abstract : Bio-based degradable supramolecular plastics with a high fracture strength of 265 MPa and excellent water-resistance are fabricated through complexation of regenerated cellulose with tannic acid, and can be fully degraded under soil in ∼35 days. Abstract : It is challenging to fabricate high-performance degradable plastics that simultaneously possess high mechanical strength, satisfactory water resistance and rapid degradation characteristics in natural environments using biomass resources. In this study, mechanically robust, water-resistant, biocompatible, and degradable plastics are fabricated through the complexation of regenerated cellulose and tannic acid (TA) followed by molding these complexes into desired shapes. The resulting plastic (denoted as C-TA) prepared with 15 wt% TA exhibits an ultrahigh fracture strength of ∼265 MPa and a toughness of ∼55.2 MJ m −3 . An all-atom molecular dynamics simulation demonstrates that the introduction of dendritic TA molecules notably enhances the toughness of the C-TA plastic through the formation of TA-centered hydrogen-bond clusters. The C-TA plastic retains a fracture strength of ∼166 MPa and ∼98 MPa after being stored in environments with relative humidities of 80% and 100% for 7 days, respectively, indicating its excellent water resistance. The good water resistance and high mechanical strength of the C-TA plastic originate from the hydrophobic aromatic rings of its TA molecules and its TA-centered hydrogen-bond clusters which serve as cross-links and nanofillers to strengthen the plastic. The C-TA plastic can be fully degraded in soil into nontoxic species within 35 days.